Témoigner de l’intérieur : l’œuvre photographique de Frankie Quinn à Belfast - Fabrice Mourlon (Revue LISA)
Born in the Short Strand, a Catholic enclave in Protestant East Belfast, Frankie Quinn is a Northern Irish photographer who gives an insider’s view of the various aspects of everyday life in Belfast in the 1980s and 1990s. His work includes portraits of individuals as well as conflict-related scenes and urban landscapes. Frankie Quinn started taking pictures of his community in 1982 when he joined a local camera club on the initiative of his father who thought this activity would shelter his son from the troubled period following the Hunger Strikes of the early 1980s. As a representative of the community photography tradition which encourages amateur photographers to represent the everyday life of their own community, Frankie Quinn shows, beyond the stereotyped images of a conflict-torn country, the joys and pains of ordinary people. Both a social documentary and a tool of political struggle, his pictures, most of which are people-centred, are in contrast with “dehumanised” photos taken by post-conflict artists from the 2000s.